A STRATEGY OF TADOF1 CASSETTE DEVELOPMENT IN PLANT EXPRESSION VECTOR TO ENHANCE NITROGEN ASSIMILATION IN WHEAT - A. Hasnain; A. Maqbool; Kauser A. Malik (Journal of Animal and Plant Sciences, 2018)
TaDof1 gene is involved in enhanced nitrogen assimilation in plants. Nitrogen assimilation is essential to the growth and development of plants as it produces large quantities of organic nitrogen including proteins, amino acids and nucleic acids. In plants functional genomic studies, gene cloning and vector construction for transformation are common procedures. The availability of effective transformation vector is one of the pre-requisites for plant transformation studies. Current research depicts the cloning of complete cassette of TaDof1 in a binary monocot expression vector (pSB219) using basic cloning strategy. The digested fragments of the vector and insert were ligated followed by transformation of ligated product in E. coli (strain DH10±). The synthetic plasmid was successfully co-transformed along with the helper plasmid pAL154 in Agrobacterium tumefaciens (strain AGL1). The plasmid constructed in this study is suitable for Agrobacterium-mediated transformation of elite wheat varieties. The study paves the way of developing transgenic TaDof1 wheat cultivars exhibiting enhanced nitrogen assimilation. transformation, Wheat transformation. (Coruzzi and Zhou, 2001). Increasing nitrogen fertilizer
Keywords: Nitrogen use efficiency; Gene cloning; Single-gene cassette construction; Agrobacterium-mediated